2018
DOI: 10.1177/2309499018772374
|View full text |Cite
|
Sign up to set email alerts
|

Similar radiological results with accelerometer-based navigation versus conventional technique in total knee arthroplasty

Abstract: Our article showed that iASSIST was safe and remains a useful tool to restore mechanical axis. However, our data demonstrated no difference in lower limb alignment and component placement between the TKA that used accelerometer-based system and those that underwent conventional method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 33 publications
3
35
0
Order By: Relevance
“…[8][9][10][15][16][17][18][19][20][21][22][23][24] Among the included studies, six were RCTs, 8,10,17,19,21,23 one was a prospective study, 16 and six were retrospective studies. 9,15,18,20,22,24 The present meta-analysis analyzed 1,454 patients with 1,551 TKAs (mean sample size, 119.31 TKAs per study). None of the included studies contained revision or failure cases.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[8][9][10][15][16][17][18][19][20][21][22][23][24] Among the included studies, six were RCTs, 8,10,17,19,21,23 one was a prospective study, 16 and six were retrospective studies. 9,15,18,20,22,24 The present meta-analysis analyzed 1,454 patients with 1,551 TKAs (mean sample size, 119.31 TKAs per study). None of the included studies contained revision or failure cases.…”
Section: Search Resultsmentioning
confidence: 99%
“…Eight studies with nine groups reported a tibial component alignment out of AE3 degrees [8][9][10]15,16,19,22,24 ; the pooled result indicated that PAD was better than CON with significant differences (OR, 0.56; 95% CI, 0.33-0.93; p ¼ 0.02; outlier percentage, PAD/CON ¼ 5.36%/10.00%) (►Fig. 2A).…”
Section: Alignment Outliers Out Of Ae2 or Ae3 Degreesmentioning
confidence: 99%
See 3 more Smart Citations